## Solving the Equation: (x+12)(x-4)=960

This article will guide you through the process of solving the quadratic equation **(x+12)(x-4)=960**.

### 1. Expanding the Equation

First, we need to expand the left side of the equation by using the distributive property (or FOIL method):

**(x+12)(x-4) = x² - 4x + 12x - 48**

Simplifying the expression:

**x² + 8x - 48 = 960**

### 2. Rearranging the Equation

To solve the quadratic equation, we need to set it equal to zero:

**x² + 8x - 1008 = 0**

### 3. Factoring the Equation

Now, we need to factor the quadratic expression. We need to find two numbers that multiply to -1008 and add up to 8. These numbers are 36 and -28:

**(x + 36)(x - 28) = 0**

### 4. Solving for x

Finally, we can solve for x by setting each factor equal to zero:

**x + 36 = 0**=>**x = -36****x - 28 = 0**=>**x = 28**

### 5. Conclusion

Therefore, the solutions to the equation **(x+12)(x-4)=960** are **x = -36** and **x = 28**.